The Effect of Micro-Abrasive Surface Treatments on Fiber Reinforced Posts. - Hamad, Mardeia. (2017)
Abstract: Abstract Objective: Post debonding is considered one of the major causes of failure associated with endodontic treated teeth with fiber posts· Micro-abrasive surface treatments have showed an improvement in the retention of the fiber posts· However’ the effect of these treatments on the flexural strength of these posts are not clear’ so the purpose of this in vitro study is to evaluate the effect of different micro-abrasions on shear bond strength of fiber posts to resin cement’ and their effect on flexural strength of fiber posts· Materials and Methods: One hundred twenty glass fiber posts (Rely X Posts) were used in this study· They were randomly divided into two groups: shear bond strength and flexural strength· Each group was divided into four subgroups according to the different micro-abrasive surface treatments: (no treatment (control) ’ 30μ cojet sand’ 50μ’ and 110μaluminum oxide) · For shear bond testing’ samples were bonded with self-adhesive cement (Rely X Unicem) · After that’ samples were stored in distilled water at 37°C for 24 hours. Shear bond strength and flexural strength were tested using a universal testing machine (Instron Model 5566A Norwood’ MA) loaded at a crosshead speed of 1.0mm/min· The Kruskal-Wallis test was conducted to analyze data for shear bond strength· Post-hoc testing was done via the Mann-Whitney U test’ while one-way ANOVA was conducted to analyze data for flexural strength· Results: A 110μ aluminum oxide micro-abrasion showed a statistically significant improvement in the shear bond strength (P < 0.001) between fiber posts and resin cement compared to the control group· All micro-abrasion surface treatment groups did not show any statistically significant reductions in the flexural strength of fiber posts (P = .091) · Conclusions: Under the limitations of this lab study, micro-abrasion with 110μ aluminum oxide provided a significant improvement in shear bond strength of glass fiber posts to resin cement without compromising their flexural strength·; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Other.; Advisors: Dr. Gerard Kugel, and Dr. Masly Harsono Harsono.; Committee: Dr. Matthew Finkelman, and Dr. Yong Jeong Kim.; Keywords: Dentistry, and Health sciences.